1996
DOI: 10.1515/bchm3.1996.377.4.239
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Changes in the Ratio of Homologous Recombination to Nonhomologous DNA-End Joining in Oocytes and Early Embryos ofXenopus laevis

Abstract: We have developed a versatile plasmid vector (pReco Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 66 publications
1
36
0
Order By: Relevance
“…Even though the oligonucleotides had 5= protruding "sticky ends," these were not necessarily used by the cell. For example, in head-to-tail or head-to-head fusions of oligonucleotides where the ends did not match each other, the new enhancers were most likely assembled by a trimming and ligation process, termed nonhomologous end joining (NHEJ) (5,11,15,30,34). An extensively trimmed junction between the XbaI site of the enhancerless SV40 and an 18-bp repeat oligonucleotide is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the oligonucleotides had 5= protruding "sticky ends," these were not necessarily used by the cell. For example, in head-to-tail or head-to-head fusions of oligonucleotides where the ends did not match each other, the new enhancers were most likely assembled by a trimming and ligation process, termed nonhomologous end joining (NHEJ) (5,11,15,30,34). An extensively trimmed junction between the XbaI site of the enhancerless SV40 and an 18-bp repeat oligonucleotide is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since Xenopus oocytes have a higher potential for homologous recombination than fertilized embryos (Hagmann et al, 1996), we next tested whether the host transfer method could be used for efficient HDR-mediated knock-in. We targeted the C-terminus of X. laevis Ctnnb1 (β-catenin), a key cytoskeletal protein and effector of the canonical Wnt pathway, because previous studies have shown that addition of epitope tags to the C-terminus do not affect the function of the resulting fusion protein ( Fig.…”
Section: Efficient Hdr-mediated Knock-in Of Epitope Tags In Oocytesmentioning
confidence: 99%
“…Since it has been reported that inhibition of DNA ligase activity enhances the rate of HDR over NHEJ in a cell type-specific and context-dependent manner (Chu et al, 2015;Hagmann et al, 1996;Maruyama et al, 2015;Song et al, 2016), we tested whether this could be used to further improve HDR-mediated knock-in efficiency in oocytes. Consistent with this hypothesis, addition of the DNA ligase inhibitor SCR-7 (5 µM) to oocyte culture medium after injection of CRISPR components into oocytes increased the rate of successful knock-in for both ctnnb1 and vangl2 from an average of 7.4% to 22% (Fig.…”
Section: Increased Efficiency Of Hdr-mediated Knock-in By Dna Ligase mentioning
confidence: 99%
See 1 more Smart Citation
“…Both processes were studied in vivo by microinjection of DNA as well as in vitro in extracts derived from various stages of oogenesis and early embryogenesis (12,18,26). In oocytes, homologous recombination is the prevalent mechanism for the joining of two linear DNA molecules and NHEJ is virtually undetectable.…”
mentioning
confidence: 99%